Growth and physiological response of amaranth seedlings to temperature and drought stress - Nuugulu, Leonard Megameno (University of the Free State, 2013)
Several environmental factors constantly play a role in crop failures. Of these high temperature and limited water supply are major factors that limit plant productivity and threatens food security. Hence, a search for alternative crops with good tolerance characteristics towards abiotic stress is an ongoing process. Amaranth has been established as an annual vegetable and grain crop and is seen as a prospective alternative crop. Seed germination and seedling development are presumed to be the most critical stages in the life cycle of many seed propagated crops. This served as a rationale for the underlying study on two amaranth species in terms of seed germination, as well as the morphological and physiological response of seedlings to different temperature (25, 30, 35, 40˚C) and water potential (0, -250, -500, -750, -1000, -1250 kPa) regimes. For A. cruentus the optimum temperature was between 25 and 30oC and between 30 and 35oC for A. hybridus in terms of seed germination and early seedling growth. A. hybridus showed a greater level of adaptation to the higher temperature regimes as well as when simultaneously exposed to a rather stringent water potential of -1250 kPa by maintaining root growth better than A. cruentus. Moreover, the imposed temperature/drought stress condition had no significant effect on either of the physiological parameters tested in the former species. These included sugar and total water soluble protein levels as well as photosynthesis and respiratory capacity. Together with the ability of stressed seedlings to maintain growth, the latter strongly suggests that the metabolic events were scarcely affected in A. hybridus, supporting the postulate that it showed a higher degree of tolerance towards abiotic stress conditions. Alternatively, more than half of these events were found to be upgraded in A. cruentus seedlings and interpreted as an attempt by this species to counteract the stress effects, but not successfully, as measured by its inability to maintain seedling growth under these stress conditions.

Verskeie omgewingsfaktore speel ‘n rol in oesverliese. Van hierdie is hoë temperatuur en beperkte watervoorsiening die hoofoorsake wat plantproduktiiteit beperk en voedselsekuriteit bedreig. Gevolglik is ‘n soeke na alternatiewe gewasse met uitstekende weerstandseienskappe t.o.v. abiotiese stremming ‘n aanhoudende proses. Amaranthus is reeds as ‘n eenjarige groente- en graangewas gevestig en word beskou as ‘n potensiële alternatiewe gewas. Saadkieming en vroeë saailingontwikkeling is van die mees kritieke ontwikkelingsfases in die lewensiklus van baie saad gepropageerde gewasse. Laasgenoemde het die rasionaal verskaf vir die onderhawige studie op twee Amaranthus species in terme van saadkieming sowel as die morfologiese en fisiologiese respons van saailinge op verskillende temperatuur (25, 30, 35, 40˚C) en water potensiaal (0, -250, -500, -750, -1000, -1250 kPa) reeks. Vir A. cruentus was die optimum temperatuur tussen 25 en 30oC en tussen 30 en 35oC vir A. hybridus in terme van beide saadkieming en vroeë saailinggroei. A. hybridus het egter ‘n hoër mate van aanpassing by die boonste gedeelte van die temperatuurreeks asook tydens die gesamentlike blootstelling aan ‘n taamlik streng waterpotensiaal van - 1250 kPa getoon deur wortelgroei beter te onderhou as A. cruentus. Meer nog het die temperatuur/droogte stremming wat opgelê is geen betekenisvolle effek op enige van die fisiologiese parameters wat getoets is in eersgenoemde spesies getoon nie. Hierdie parameters het suiker en totale wateroplosbare proteïen inhoud asook fotosintese en respirasiepotensiaal ingesluit. Tesame met die vermoë van gestremde saailinge om groei te onderhou, onder hierdie omstandighede, ondersteun laasgenoemde die postulaat dat metaboliese aktiwiteite skaars in A. hybridus beïnvloed is en dat hierdie spesies inherent oor ‘n hoër mate van weerstand teen abiotiese stremmingsfaktore beskik. Alternatiewelik is meer as die helfte van die fisiologiese prosesse deur die stremming in A. cruentus saailinge verhoog wat slegs geïnterpreteer word as ‘n poging deur die spesies om die stremming teë te werk maar sonder sukses, gemeet aan die onvermoë om saailinggroei te onderhou onder hierdie omstandighede.
Dissertation (M.Sc.Agric. (Soil, Crop and Climate Sciences))--University of the Free State, 2013
Keywords: Seedling growth; Drought stress; Metabolic response; Heat stress; Amaranth; Seed germination; Amaranths -- Drought tolerance; Amaranths -- Growth